Always remember ebook Ben's story. - Balogh, Mary (Ravenswood, 2024)
Lady Jennifer Arden and Ben Ellis know that a match between them is out of the question. Yet their hearts yearn for the impossible. Discover a new heartwarming story from New York Times bestselling author and beloved “queen of Regency romance” Mary Balogh. Left unable to walk by a childhood illness, Lady Jennifer, sister of the Duke of Wilby, has grown up to make a happy place for herself in society. Outgoing and cheerful, she has many friends and enjoys the pleasures of high society—even if she cannot dance at balls or stroll in Hyde Park. She is blessed with a large, loving, and protective family. But she secretly dreams of marriage and children, and of walking—and dancing. When Ben Ellis comes across Lady Jennifer as she struggles to walk with the aid of primitive crutches, he instantly understands her yearning. He is a fixer. It is often said of him that he never saw a practical problem he did not have to solve. He wants to help her discover independence and motion—driving a carriage, swimming, even walking a different way. But he must be careful. He is the bastard son of the late Earl of Stratton. Though he was raised with the earl’s family, he knows he does not really belong in the world of the ton. Jennifer is shocked—and intrigued—by Ben’s ideas, and both families are alarmed by the growing friendship and perhaps more that they sense developing between the two. A duke’s sister certainly cannot marry the bastard son of an earl. Except sometimes, love can find a way.